The Methodological Meaning of the Dialectical Conception of Determinism - Meškauskas, Eugenijus (Problemos, 1984)
In the article the necessity of evaluation of the principle of the universal relationship of phenomena while discussing the methodological contents of the dialectical conception of determinism, as well as its difference from the contents of mechanistic determinism are demonstrated. The same is true for the categories that are closely linked with the methodological usage of determinism.